Potensi Teknologi Nanopartikel Logam Seng Oksida (NP-ZnO) pada Obat Anti-TB Sebagai Modalitas Mutakhir Pengobatan Penyakit Multidrug-Resistant Tuberculosis (MDR-TB) - Adinda Nezma Meidina; Akbar Triandra; Nabila Az-zahra Hasibuan; M. Alif Al Fajri (Scripta Score Scientific Medical Journal, 2024)
Background: Tuberculosis (TB) is a treatable infectious disease caused by the Mycobacterium tuberculosis pathogen. However, patient non-compliance during treatment contributes to the emergence of Multidrug-resistant Tuberculosis (MDR-TB). This literature review aims to further explore the potential of zinc oxide metal nanoparticles (NP-ZnO) in anti-TB drugs as an advanced modality for MDR-TB treatment by enhancing drug efficacy, reducing intestine degradation, and increasing absorption and bioavailability. Methods: Literature was searched using search engines such as Google Scholar, Science Direct, ResearchGate, and NCBI. Inclusion and exclusion criteria were applied, resulting in 14 relevant articles. Results and Discussion: Zinc oxide metal nanoparticles (NP-ZnO) exhibit antibacterial effects. Studies show that NP-ZnO can decrease Rifampicin's minimum inhibitory concentration (MIC) fourfold by enhancing bacterial cell membrane permeability and increasing bactericidal effects through interactions with host macrophage cells. Bactericidal effects were found with NP-ZnO and its combination with selenium (NP ZnO-Se). Meanwhile, bacteriostatic effects on MDR-TB and XDR-TB were observed with NP-ZnO and its combination with silver (NP Ag-ZnO). Conclusion: NP-ZnO encapsulated first-line anti-TB drugs offer advantages in delivering medication to target organs, accelerating therapy onset even with smaller doses, and mimicking M.tb's activity in infecting target organs. NP-ZnO and its combinations are also more sensitive in interacting with alveolar macrophages, the first immune cells responding to M.tb. NP-ZnO encapsulated first-line anti-TB drug technology holds potential as an advanced modality for MDR-TB treatment.